Improving Struggling Fifth-Grade Students' Understanding of Fractions: A Randomized Controlled Trial of an Intervention That Stresses Both Concepts and Procedures. (October 2021) - Jayanthi, Madhavi; Gersten, Russell; Schumacher, Robin F.; Dimino, Joseph; Smolkowski, Keith; Spallone, Samantha
Using a randomized controlled trial, we examined the effect of a fractions intervention for students experiencing mathematical difficulties in Grade 5. Students who were eligible for the study ( n = 205) were randomly assigned to intervention and comparison conditions, blocked by teacher. The intervention used systematic, explicit instruction and relied on linear representations (e.g., Cuisenaire Rods and number lines) to demonstrate key fractions concepts. Enhancing students' mathematical explanations was also a focus. Results indicated that intervention students significantly outperformed students from the comparison condition on measures of fractions proficiency and understanding ( g = 0.66–0.78), number line estimation ( g = 0.80–1.08), fractions procedures ( g = 1.07), and explanation tasks ( g = 0.68–1.23). Findings suggest that interventions designed to include explicit instruction, along with consistent use of the number line and opportunities to explain reasoning, can promote students' proficiency and understanding of fractions.